A case-crossover study of air pollution exposure during pregnancy and the risk of stillbirth in Tehran, Iran - Nadia Mohammadi Dashtaki; Mohammad Fararouei; Alireza Mirahmadizadeh; Mohammad Hoseini; Mohammad Heidarzadeh (Scientific Reports)
Abstract The growing fetus is very sensitive to environmental conditions. There is limited and conflicting evidence about the short-term effects of exposure to air pollutants on the pregnancy outcome. In this time-stratified case-crossover study, the effect of several air pollutants (i.e. O3, CO, NO2, SO2, and PM2.5) on the occurrence of stillbirth was evaluated in Tehran (the capital of Iran) between December 2018 and March 2023. Using a quasi-Poisson regression model and distributed lag nonlinear models (DLNM), we estimated the effect of exposure to air pollutants measured as lags (0 to 7 days) and cumulative average days (0–2, 0–6, and 0–14-day lag) before delivery on stillbirth. The association was adjusted for potential confounding factors including meteorological factors. During the study period in Tehran, 5311 stillbirths were reported. In single-pollutant models, during the entire year, SO2 (lag 1 day) and NO2 (lag 2 days) were found to have a direct and significant relationship with stillbirth. In the warm seasons, we found direct and inverse relationships between NO2 (lag 2 days) and PM2.5 (lag 4 days), respectively. In cold seasons, PM 2.5 (lag 1 day) and cumulative lag (0–2 days), SO2 (lag 1 day), and cumulative lag (0–2 and 0–6 days) were found to have direct and significant relationships with stillbirth. In two-pollutant models, SO2 & CO, and SO2 & O3, direct and significant associations were observed between SO2 exposures and stillbirth for the entire year. A similar pattern was observed for PM2.5 in combinations with NO2, and O3 and for NO2 in the two-pollutant model (O3 & NO2). However, in warm seasons, inverse associations were observed between PM2.5 and stillbirth in combinations with O3, NO2, and SO2, while NO2 showed a direct association in combinations with PM2.5, CO, and O3. In the cold seasons, direct and significant associations were observed between SO2 and stillbirth in model combinations with CO, O3, and NO2. This relationship was observed for PM2.5 in combination with CO, and NO2. Also, for CO in the two-pollutant model of CO & NO2. As a result, this study showed evidence of a relationship between short-term exposure to ambient air pollution before birth, especially SO2, NO2, PM2.5, and CO with increased risk of stillbirth.